Collaborative Community Approaches to Addressing Serious Violence - Mallion, Jaimee; Gebo, Erika (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The World Health Organization (2002) classified violence as a leading international public health problem that requires immediate intervention. Violence is a pervasive social problem whose causes and consequences are inextricably linked to individuals, families, institutions, communities, and societies. The negative consequences of violence, and serious violence in particular, reverberate beyond the immediate moment and location of it. By bringing together partners with varied skills, whole-system multiagency approaches are advocated as the leading means of targeting serious violence. With this context in mind, this Special Issue examines a variety of collaborative, community-based approaches to preventing and reducing serious violence across the global landscape. The contributions from practitioners and researchers focus on the prevention and reduction of serious interpersonal violence in communities. The typologies of serious violence discussed by the collaborators include gang membership, domestic violence, and sexual violence. The contributions address the collaborative nature of serious violence prevention work, recognizing that violence is multicausal and that solutions are needed across various socioecological domains. The contributions describe community-level collaborative approaches to preventing and reducing serious violence. The successes and lessons learned from the approaches are identified, and the applicability of the approaches to other areas are explored.